A PVC / ABS alloy material with high heat resistance, high flame retardant efficiency and low acid separation and a preparation method and application thereof

CN121699308BActive Publication Date: 2026-10-09GUANGZHOU SUPER DRAGON ENG PLASTICS +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511973942.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-25
Publication Date
2026-10-09
Estimated Expiration
2045-12-25

AI Technical Summary

Technical Problem

目前市面上的PVC/ABS仍有以下几点问题:①PVC与ABS的加工温度区间存在一定差别,较低的加工温度无法很好的将ABS材料完全熔融,导致材料的加工性不足,有时甚至能在加工时看到明显的未融ABS小块物,较高的加工温度又会使得PVC在加工过程中出现明显降解现象,需要额外添加PVC热稳定剂,增加了使用成本;②面对较高的耐热要求,如维卡软化点85℃以上这种情况,往往需要增大PVC/ABS材料中的ABS比例,一般会达到40%以上,同时需要改用较高耐热的低流动性ABS,这会导致材料熔指过低,加大了加工难度,另一方面增加ABS材料的比例会导致阻燃效果的明显下降,且由于过多的ABS组分导致了阻燃不稳定,需要额外添加三氧化二锑等协效阻燃剂维持阻燃效果,增加了额外的成本;③PVC/ABS材料在使用过程中常用于电子电器的电控盒,其与电路板常常需要直接接触,但PVC/ABS材料在长期使用过程中易析出酸性气体或液体腐蚀电路板,导致产品使用寿命下降

Benefits of technology

(1)本发明所述高耐热、高阻燃效率、低析酸性的PVC/ABS合金材料优选了ABS树脂与PVC树脂的种类及相对比例,选择连续本体法生产的ABS树脂,其耐热与刚性更佳,更有助于材料的耐热温度提高,充分平衡其阻燃与耐热需求,使其能在耐热维卡软化点85℃的高要求下达到2.0mm V0的阻燃需求;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a PVC / ABS alloy material with high heat resistance, high fire resistance efficiency and low acid separation and a preparation method and application thereof. The alloy material is composed of the following components in mass percentage: PVC resin 30.0-50.0 %, ABS resin 25.0-45.0 %, AS resin 10.0-20.0 %, modified composite flame retardant 5.0-10.0 %, toughening agent 3.0-8.0 %, processing aid 1.0-3.0 %, heat stabilizer 1.0-2.0 %, lubricant 0.1-0.5 %, and antioxidant 0.1-0.5 %, and the sum of the mass percentages of the components is 100 %. The PVC / ABS alloy material prepared by the application has a wide application prospect in electronic and electrical control components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of modified plastic materials, specifically relating to a PVC / ABS alloy material with high heat resistance, high flame retardancy, and low acidity, as well as its preparation method and application. Background Technology

[0002] Polyvinyl chloride (PVC) is widely used in the market due to its low price, excellent corrosion resistance, superior flame retardant properties, and diverse processing methods. PVC materials cover many aspects, including infrastructure products, household appliances, and cable conduits. However, PVC also has significant drawbacks. On the one hand, PVC has poor stability and is easily affected by light or high heat. The decomposition product, hydrogen chloride (HCl), further accelerates the degradation of PVC. On the other hand, PVC has a low softening temperature and poor heat resistance, which limits its effectiveness in high-temperature environments.

[0003] Acrylonitrile-butadiene-styrene copolymer (ABS) has a good balance of rigidity and toughness, is easy to process and mold, and its relatively low shrinkage rate also results in good dimensional stability after molding. However, due to its special ternary chemical structure, flame-retardant modification of ABS is difficult, usually requiring the addition of a large amount of flame retardant to achieve the desired effect. This leads to the shortcomings of flame-retardant ABS in terms of cost and physical properties.

[0004] Combining the advantages of both materials and complementing their disadvantages, PVC / ABS alloy materials are currently available on the market through blending and modification of ABS and PVC. These materials possess both the excellent flame-retardant properties of PVC, enabling them to meet high flame-retardant requirements, and the heat and impact resistance of ABS. They are widely used in electronic and electrical control boxes and housings.

[0005] While PVC / ABS materials have these advantages, consumers' increasingly higher quality requirements also place higher demands on the materials. Currently, PVC / ABS on the market still has the following problems: ① There is a certain difference in the processing temperature range between PVC and ABS. Lower processing temperatures cannot completely melt ABS material, resulting in insufficient processability. Sometimes, even obvious unmelted ABS pieces can be seen during processing. Higher processing temperatures will cause significant degradation of PVC during processing, requiring the addition of PVC heat stabilizers, which increases the cost of use. ② For high heat resistance requirements, such as a Vicat softening point above 85℃, it is often necessary to increase the proportion of ABS in the PVC / ABS material, generally reaching more than 40%. At the same time, it is necessary to use ABS with higher heat resistance and lower fluidity. This will result in a low melt index, increasing the processing difficulty. On the other hand, increasing the proportion of ABS material will lead to a significant decrease in flame retardancy. Moreover, due to the excessive ABS component, the flame retardancy is unstable, requiring the addition of antimony trioxide and other synergistic flame retardants to maintain the flame retardancy effect, which increases additional costs. ③ PVC / ABS material is often used in the electrical control boxes of electronic appliances, which often need to be in direct contact with circuit boards. However, PVC / ABS material is prone to releasing acidic gases or liquids that corrode circuit boards during long-term use, leading to a reduction in product lifespan. Summary of the Invention

[0006] To address the shortcomings and deficiencies of existing technologies, the primary objective of this invention is to provide a PVC / ABS alloy material with high heat resistance, high flame retardancy, and low acid precipitation. This alloy material exhibits relatively excellent heat resistance, stable flame retardancy, low long-term acid precipitation, and high injection molding efficiency, meeting the needs of industrial production and possessing a wide range of applications.

[0007] The second objective of this invention is to provide a method for preparing a PVC / ABS alloy material with high heat resistance, high flame retardancy, and low acidity.

[0008] The third objective of this invention is to provide an application of a PVC / ABS alloy material with high heat resistance, high flame retardancy, and low acidity.

[0009] The primary objective of this invention is achieved through the following technical solution: A PVC / ABS alloy material with high heat resistance, high flame retardancy, and low acidity is composed of the following components by mass percentage: PVC resin 30.0-50.0% ABS resin 25.0~45.0% AS resin (styrene-acrylonitrile copolymer) 10.0~20.0% Modified composite flame retardant 5.0–10.0% Toughening agent 3.0–8.0% Processing aids 1.0–3.0% Heat stabilizer 1.0–2.0% Lubricant 0.1-0.5% Antioxidant 0.1-0.5%; The sum of the mass percentages of the above components is 100%; The modified composite flame retardant is a mixture of brominated triazine, magnesium aluminum hydrotalcite, and calcium aluminum hydrotalcite, which is prepared by in-situ precipitation and coating modification of phytic acid / sodium phytate solution and zinc sulfate solution during high mixing.

[0010] Preferably, the preparation method of the modified composite flame retardant includes the following preparation steps: (a) Prepare a 0.6-1.0 mol / L phytic acid / sodium phytate solution and a 0.6-1.0 mol / L zinc sulfate solution; (b) The mixture of bromotriazine and hydrotalcite is mixed at high speed to obtain a common composite flame retardant; the mass fraction of bromotriazine in the common composite flame retardant is 30~50%; the hydrotalcite mixture is a mixture of magnesium aluminum hydrotalcite and calcium aluminum hydrotalcite in any mass ratio; (c) The ordinary composite flame retardant prepared in step (b) is sprayed into a high-speed mixer through two spray nozzles using a sprayer to mix the phytic acid / sodium phytate solution and zinc sulfate solution prepared in step (a) at high speed. This allows the phytic acid / sodium phytate solution and zinc sulfate solution to react on the surface of the ordinary composite flame retardant, causing zinc phytate to precipitate in situ on the surface of the ordinary composite flame retardant mixture. The mixture is then aged and dried to obtain the modified composite flame retardant.

[0011] Preferably, the high-speed mixing speed in step (b) is 800-1500 rpm, and the high-speed mixing time is 1-2 min.

[0012] Preferably, in step (c), the high-speed mixing speed is 800-1500 rpm, the high-speed mixing time is 1-3 min, the aging time is 60-100 min, and the drying temperature is 60-80℃.

[0013] Preferably, the PVC resin is SG-8 type resin powder with a degree of polymerization of 650~750.

[0014] Preferably, the ABS resin is an ABS resin produced by a continuous bulk method.

[0015] Preferably, the processing aid is an acrylate copolymer (ACR-401) with a weight-average molecular weight of 250,000 to 750,000. The processing aid is used to promote the plasticization of PVC during processing.

[0016] Preferably, the toughening agent is a mixture of chlorinated polyethylene (CPE) and methyl methacrylate-butadiene-styrene terpolymer (MBS) in any mass ratio.

[0017] Preferably, the CPE is type 135C, and the MBS is toughened MBS.

[0018] Preferably, the heat stabilizer is at least one of organotin heat stabilizers and stearate heat stabilizers.

[0019] Preferably, the lubricant is at least one of silicone-based lubricants, fatty acid amides, metal stearates, waxes, and esters.

[0020] Preferably, the antioxidant is at least one of hindered phenolic antioxidants, thioester antioxidants, phosphite antioxidants, and ester antioxidants.

[0021] The second objective of this invention is achieved through the following technical solution: A method for preparing a PVC / ABS alloy material with high heat resistance, high flame retardancy, and low acidity includes the following steps: (1) PVC resin, modified composite flame retardant, processing aid, toughening agent, heat stabilizer, antioxidant and lubricant are mixed at high speed to 80°C to obtain premix I; (2) Add ABS resin and AS resin to premix I and mix at high speed to 100°C to obtain premix II; (3) Add premix II from the main feed port of the twin-screw extruder, melt extrude and granulate, cool, air dry, granulate, vibrate and sieve, and homogenize to prepare PVC / ABS alloy material with high heat resistance, high flame retardancy and low acidity. The high-speed mixing speed described in steps (1) and (2) is 800-1500 rpm; In step (3), the temperatures of each section of the twin-screw extruder are set to 130℃, 150℃, 180℃, 170℃, 165℃, 160℃, 155℃, and 150℃, the die head temperature is 170℃, and the screw speed is 200-250 rpm.

[0022] The third objective of this invention is achieved through the following technical solution: Application of a PVC / ABS alloy material with high heat resistance, high flame retardancy, and low acidity in electronic and electrical control components.

[0023] Specifically, the electronic and electrical control components can be electronic connectors, control boxes, low-voltage switches, housings, and electrical structural parts.

[0024] Compared with the prior art, the present invention has the following advantages and beneficial effects: (1) The PVC / ABS alloy material with high heat resistance, high flame retardancy efficiency and low acidity described in this invention has the preferred type and relative ratio of ABS resin and PVC resin. The ABS resin produced by the continuous bulk method is selected, which has better heat resistance and rigidity, and is more conducive to improving the heat resistance temperature of the material. It fully balances its flame retardancy and heat resistance requirements, so that it can achieve the flame retardancy requirement of 2.0 mm V0 under the high requirement of heat resistance Vicat softening point of 85℃. (2) The high heat resistance, high flame retardancy and low acidity of the PVC / ABS alloy material described in this invention, based on the traditional ABS+PVC system, also selects to use some AS resin to replace ABS resin, which helps to improve the overall heat resistance of the material and improve the fluidity during processing, reducing the decomposition phenomenon during material processing. (3) Due to supply and demand imbalance, there is a severe shortage of antimony trioxide materials on the market, and the price of antimony trioxide has repeatedly reached new highs, which has led to significant obstacles in the application of PVC / ABS alloy materials. In this invention, a modified composite flame retardant is used to replace antimony trioxide in the traditional PVC / ABS system with high ABS resin content, and the same flame retardant effect can be achieved, which improves the price competitiveness of the material. (4) The modified composite flame retardant used in this invention selects bromotriazine as an auxiliary synergistic flame retardant for PVC / ABS flame retardancy. It effectively fills the gap caused by the low PVC content due to high heat resistance requirements, resulting in unstable flame retardancy. Compared with other phosphorus-based antimony substitutes on the market, bromotriazine directly increases the halogen content in the material, and its effect of improving flame retardancy efficiency is significantly better than other antimony substitutes. (5) The modified composite flame retardant used in this invention also contains magnesium aluminum hydrotalcite and calcium aluminum hydrotalcite. On the one hand, it can effectively improve the thermal stability of the material, so that PVC / ABS can remain stable even when processed at higher temperatures. On the other hand, magnesium aluminum hydrotalcite and calcium aluminum hydrotalcite are natural acid absorbers. During long-term use, they can capture the acidic gases and liquids generated, preventing corrosion of metal items such as circuit boards that come into contact with PVC / ABS materials. In addition, due to its special physicochemical structure, hydrotalcite decomposes during combustion to release carbon dioxide and water, which can absorb heat and cool down. The metal oxides (magnesium oxide and aluminum oxide) produced by decomposition can form dense oxides, preventing heat and oxygen conduction and improving flame retardant efficiency. (6) The modified composite flame retardant used in this invention will form a special in-situ precipitate of zinc phytate after being treated with phytic acid / sodium phytate and zinc sulfate solution. On the one hand, zinc phytate is an excellent flame retardant and smoke suppressant with sufficient phosphorus content, which can improve flame retardant efficiency. On the other hand, the in-situ precipitate of zinc phytate produced by special treatment has a better flame retardant ability than the effect of directly adding zinc phytate. (7) In the in-situ precipitation treatment of the modified composite flame retardant, zinc sulfate is preferred as the zinc salt solution for the reaction. The by-product sodium sulfate after the reaction has no significant effect on the overall thermal stability and flame retardancy of the PVC / ABS alloy material. Detailed Implementation

[0025] The present invention will be further described in detail below with reference to embodiments, but the embodiments of the present invention are not limited thereto. All raw materials involved in the present invention can be purchased directly from the market. For process parameters not specifically specified, conventional techniques can be referred to.

[0026] The raw materials used in the embodiments and comparative examples of this invention are as follows: Polyvinyl chloride (PVC resin): TL-700, Bohai LG; Acrylonitrile-butadiene-styrene copolymer (ABS resin): ABS 3504, Sinopec; Styrene-acrylonitrile copolymer (AS resin): SAN 2437, PetroChina Jilin Chemical Co., Ltd. Bromotriazine: RDT-8, Shouguang Weidong Chemical Co., Ltd.; Magnesium aluminum hydrotalcite, calcium aluminum hydrotalcite: HG-200, HG-201, Hunan Hengguang; Calcium carbonate: DN2500, southeast of Lianzhou; Inositol hexaphosphate (phytic acid): Commercially available and universally applicable; Chlorinated polyethylene (CPE): CPE135C, Shandong Ruifeng Polymer Materials Co., Ltd.; methyl methacrylate-butadiene-styrene terpolymer (MBS): LB-166, Ruifeng Polymer Materials Co., Ltd.; Acrylic ester polymer copolymer: ACR-401, commercially available and universal; Organotin heat stabilizer: Methyltin mercaptan, commercially available and generally applicable; Glyceryl monostearate: Commercially available and generally accepted; Main antioxidant: 1098 (N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexamethylenediamine), Ciba, Switzerland; Co-antioxidant: 168 (tris(2,4-di-tert-butylphenyl)phosphite), Ciba, Switzerland.

[0027] In the preparation process of the high heat resistance, high flame retardancy efficiency, and low acidity PVC / ABS alloy materials described in Examples 1 to 7 of this invention, the modified composite flame retardant used is prepared according to the following steps: (a) Prepare a 0.6-1.0 mol / L phytic acid / sodium phytate solution and a 0.6-1.0 mol / L zinc sulfate solution; (b) Bromotriazine, magnesium aluminum hydrotalcite, and calcium aluminum hydrotalcite are mixed at a mass ratio of 3:3.5:3.5 at high speed. The high-speed mixing speed is 800-1500 rpm and the high-speed mixing time is 60s to obtain a common composite flame retardant. (c) The ordinary composite flame retardant prepared in step (b) is sprayed into a high-speed mixer through two nozzles: phytic acid / sodium phytate solution and zinc sulfate solution. The speed of the high-speed mixer is 800-1500 rpm and the mixing time in the high-speed mixer is 3 min. This allows the phytic acid / sodium phytate solution and zinc sulfate solution to react on the surface of the mixed powder, allowing zinc phytate to precipitate in situ on the surface of the ordinary composite flame retardant. The mixture is then aged for 60 min and dried at 80°C to obtain the modified composite flame retardant.

[0028] Raw materials were weighed according to the formulas described in Table 1, and then the high heat resistance, high flame retardancy efficiency, and low acid precipitation PVC / ABS alloy material of the present invention was prepared. The preparation method of the high heat resistance, high flame retardancy efficiency, and low acid precipitation PVC / ABS alloy material described in Examples 1 to 7 of the present invention includes the following steps: (1) PVC resin, modified composite flame retardant, processing aid, toughening agent, heat stabilizer, antioxidant and lubricant are mixed at high speed to 80°C to obtain premix I; the high speed mixing speed is 800-1500 rpm; (2) Add ABS resin and AS resin to premix I and mix at high speed to 100°C to obtain premix II; the high speed mixing speed is 800-1500 rpm; (3) Add premix II from the main feed port of the twin-screw extruder, melt extrude and granulate, cool, air dry, pelletize, vibrate and sieve, and homogenize to prepare a PVC / ABS alloy material with high heat resistance, high flame retardancy efficiency and low acidity; the temperature of each section of the twin-screw extruder is set to 130℃, 150℃, 180℃, 170℃, 165℃, 160℃, 155℃ and 150℃, the die head temperature is 170℃, and the screw speed is 200-250 rpm.

[0029] Those skilled in the art, combining conventional knowledge with reference to the above preparation steps, can make adaptive modifications based on the formulations described in Examples 1 to 7 in Table 1.

[0030] Table 1

[0031] Note: Density was tested according to ISO 1183-1 standard; melt flow index was tested according to ISO 1133-1:2022 standard; Vicat softening point was tested according to ISO 306:2022 standard, condition B120; the dynamic thermal stability time test method was to use a torque rheometer to perform long-term mixing under test conditions of 190℃ and 60RPM, and the time difference between the time point when the torque curve suddenly rises and the time point when the material is added was taken as the dynamic thermal stability time. The longer the time, the better the thermal stability of the material; the acid precipitation pH test method was to take 25g of material particles of equal mass from each formula and place them in a sealed beaker, add 100ml of deionized water, heat in an 80℃ water bath, and record the pH of the solution using a pH meter after 168 hours; the 2.0mm flame retardant rating test standard was the UL94 vertical burning test standard.

[0032] As shown in Table 1 above, Example 1 demonstrates that the high-PVC-content PVC / ABS alloy material exhibits excellent flame retardancy but poor heat resistance, with a Vicat softening point of only 76°C. Furthermore, it suffers from severe acid precipitation, easily corroding the circuit boards it contacts under long-term use. Comparing Examples 2 and 3, even with a fixed PVC content of 35% and an increased ABS ratio, the Vicat softening point still falls short of the requirement at only 83.4°C, and the flame retardancy drops drastically from V-0 to HB, failing to meet usage requirements. However, replacing some of the ABS resin with AS resin improves overall heat resistance to 87.6°C due to the increased acrylonitrile content. Comparing Examples 3 and 4, changing the filler from calcium carbonate to a composite filler of magnesium aluminum hydrotalcite and calcium aluminum hydrotalcite has little impact on heat resistance, but significantly extends the dynamic thermal stability time. The flame retardant rating of the material increased from HB to V-2, and the effect of inhibiting acid precipitation was obvious. After acid precipitation, the pH of the solution was only 6.0, close to neutral. This is consistent with the characteristics of hydrotalcite absorbing acid and improving the thermal stability and flame retardant performance of PVC. However, the flame retardant rating still did not reach V-0. Comparing Examples 4 to 6, it can be seen that adding a certain proportion of antimony trioxide or using a composite flame retardant of bromotriazine with magnesium aluminum hydrotalcite or calcium aluminum hydrotalcite can effectively improve the flame retardant rating of the material and improve the flame retardant effect. However, the flame retardant effect of the unmodified composite flame retardant is not stable enough. There are often phenomena of over-burning, which leads to failure of the flame retardant test, resulting in the material not being able to reach the V-0 rating. There is still a bottleneck in practical application. Comparing Examples 6 and 7, it can be seen that after changing the ordinary composite flame retardant to the modified composite flame retardant modified by phytic acid / zinc salt in-situ precipitation, the flame retardant effect is significantly improved, and the flame retardant rating reaches the V-0 level.

[0033] In summary, Example 1 of this invention is essentially a conventional control, demonstrating that conventional PVC / ABS formulations cannot achieve the high heat resistance, high flame retardancy efficiency, and low acidity required by this invention. Example 2 optimizes the ABS ratio in the PVC / ABS mixture, effectively improving heat resistance but sacrificing flame retardancy. Example 3 further improves heat resistance by replacing part of the ABS resin with AS resin. Example 4 optimizes acid absorption by using magnesium aluminum hydrotalcite and calcium aluminum hydrotalcite as fillers. Comparing Examples 5 and 6, it can be seen that using a composite flame retardant made from brominated triazine with magnesium aluminum hydrotalcite and calcium aluminum hydrotalcite effectively improves the flame retardancy rating. However, using only this ordinary composite flame retardant cannot compare to adding antimony trioxide flame retardant, as its flame retardant effect is not stable enough and cannot achieve a stable V0 effect. This leads to the processing method in Example 7, which ultimately achieves a good flame retardant effect. The entire process is an optimization and selection process, with each example being an optimization based on the previous example.

[0034] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A PVC / ABS alloy material with high heat resistance, high flame retardancy, and low acidity, characterized in that, It consists of the following components by mass percentage: PVC resin 30.0-50.0% ABS resin 25.0~45.0% AS resin 10.0~20.0% Modified composite flame retardant 5.0–10.0% Toughening agent 3.0–8.0% Processing aids 1.0–3.0% Heat stabilizer 1.0–2.0% Lubricant 0.1-0.5% Antioxidant 0.1-0.5%; The sum of the mass percentages of the above components is 100%; The modified composite flame retardant is a mixture of brominated triazine, magnesium aluminum hydrotalcite, and calcium aluminum hydrotalcite, which is prepared by in-situ precipitation and coating modification of phytic acid / sodium phytate solution and zinc sulfate solution during high mixing.

2. The PVC / ABS alloy material with high heat resistance, high flame retardancy, and low acidity as described in claim 1, characterized in that, The preparation method of the modified composite flame retardant includes the following preparation steps: (a) Prepare a 0.6-1.0 mol / L phytic acid / sodium phytate solution and a 0.6-1.0 mol / L zinc sulfate solution; (b) The mixture of bromotriazine and hydrotalcite was mixed at high speed to obtain a common composite flame retardant; The mass fraction of bromotriazine in the ordinary composite flame retardant is 30-50%; the hydrotalcite mixture is a mixture of magnesium aluminum hydrotalcite and calcium aluminum hydrotalcite in any mass ratio. (c) The ordinary composite flame retardant prepared in step (b) is sprayed into a high-speed mixer through two spray nozzles using a sprayer to mix the phytic acid / sodium phytate solution and zinc sulfate solution prepared in step (a) at high speed. This allows the phytic acid / sodium phytate solution and zinc sulfate solution to react on the surface of the ordinary composite flame retardant, causing zinc phytate to precipitate in situ on the surface of the ordinary composite flame retardant mixture. The mixture is then aged and dried to obtain the modified composite flame retardant.

3. The PVC / ABS alloy material with high heat resistance, high flame retardancy, and low acidity as described in claim 1, characterized in that, The PVC resin is SG-8 type resin powder with a degree of polymerization of 650~750.

4. The PVC / ABS alloy material with high heat resistance, high flame retardancy, and low acidity as described in claim 1, characterized in that, The ABS resin is an ABS resin produced by a continuous bulk method.

5. The PVC / ABS alloy material with high heat resistance, high flame retardancy, and low acidity as described in claim 1, characterized in that, The processing aid is an acrylate copolymer with a weight-average molecular weight of 250,000 to 750,000.

6. The PVC / ABS alloy material with high heat resistance, high flame retardancy, and low acidity as described in claim 1, characterized in that, The toughening agent is composed of chlorinated polyethylene and methyl methacrylate-butadiene-styrene terpolymer mixed in any mass ratio.

7. The PVC / ABS alloy material with high heat resistance, high flame retardancy, and low acidity according to claim 1, characterized in that, The heat stabilizer is at least one of organotin heat stabilizers and stearate heat stabilizers; the lubricant is at least one of silicon-based lubricants, fatty acid amides, metal stearates, waxes, and ester lubricants.

8. The PVC / ABS alloy material with high heat resistance, high flame retardancy, and low acidity according to claim 1, characterized in that, The antioxidant is at least one of hindered phenolic antioxidants, thioester antioxidants, phosphite antioxidants, and ester antioxidants.

9. A method for preparing a PVC / ABS alloy material with high heat resistance, high flame retardancy, and low acidity according to any one of claims 1 to 8, characterized in that, Includes the following steps: (1) PVC resin, modified composite flame retardant, processing aid, toughening agent, heat stabilizer, antioxidant and lubricant are mixed at high speed to 80°C to obtain premix I; (2) Add ABS resin and AS resin to premix I and mix at high speed to 100°C to obtain premix II; (3) Add premix II from the main feed port of the twin-screw extruder, melt extrude and granulate, cool, air dry, granulate, vibrate and sieve, and homogenize to prepare PVC / ABS alloy material with high heat resistance, high flame retardancy and low acidity. The high-speed mixing speed described in steps (1) and (2) is 800-1500 rpm; In step (3), the temperatures of each section of the twin-screw extruder are set to 130℃, 150℃, 180℃, 170℃, 165℃, 160℃, 155℃, and 150℃, the die head temperature is 170℃, and the screw speed is 200-250 rpm.

10. The application of a PVC / ABS alloy material with high heat resistance, high flame retardancy, and low acidity as described in any one of claims 1 to 8 in electronic and electrical control components.

Citation Information

Patent Citations

  • Flame retardant and antistatic ABS / PVC alloy material, and preparation method thereof

    CN102477206A

  • Halogen-free composite flame retardant as well as preparation method and application thereof

    CN116574309A